Epigenetic telomere protection by Drosophila DNA damage response pathways. - Oikemus, S.R.; Queiroz-Machado, J.; Lai, K.J.; McGinnis, N.; Sunkel, C.; Brodsky, M.H. (PLoS Genetics, 2006)
Analysis of terminal deletion chromosomes indicates that a sequence-independent mechanism regulates protection of Drosophila telomeres. Mutations in Drosophila DNA damage response genes such as atm/tefu, mre11, or rad50 disrupt telomere protection and localization of the telomere-associated proteins HP1 and HOAP, suggesting that recognition of chromosome ends contributes to telomere protection. However, the partial telomere protection phenotype of these mutations limits the ability to test if they act in the epigenetic telomere protection mechanism. We examined the roles of the Drosophila atm and atr-atrip DNA damage response pathways and the nbs homolog in DNA damage responses and telomere protection. As in other organisms, the atm and atr-atrip pathways act in parallel to promote telomere protection. Cells lacking both pathways exhibit severe defects in telomere protection and fail to localize the protection protein HOAP to telomeres. Drosophila nbs is required for both atm- and atr-dependent DNA damage responses and acts in these pathways during DNA repair. The telomere fusion phenotype of nbs is consistent with defects in each of these activities. Cells defective in both the atm and atr pathways were used to examine if DNA damage response pathways regulate telomere protection without affecting telomere specific sequences. In these cells, chromosome fusion sites retain telomere-specific sequences, demonstrating that loss of these sequences is not responsible for loss of protection. Furthermore, terminally deleted chromosomes also fuse in these cells, directly implicating DNA damage response pathways in the epigenetic protection of telomeres. We propose that recognition of chromosome ends and recruitment of HP1 and HOAP by DNA damage response proteins is essential for the epigenetic protection of Drosophila telomeres. Given the conserved roles of DNA damage response proteins in telomere function, related mechanisms may act at the telomeres of other organisms.